2014
DOI: 10.1117/12.2052912
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol MTF revisited

Abstract: Different views of the significance of aerosol MTF have been reported. For example, one recent paper [OE, 52(4)/2013, pp. 046201] claims that the aerosol MTF "contrast reduction is approximately independent of spatial frequency, and image blur is practically negligible". On the other hand, another recent paper [JOSA A, 11/2013[JOSA A, 11/ , pp. 2244[JOSA A, 11/ -2252 claims that aerosols "can have a non-negligible effect on the atmospheric point spread function". We present clear experimental evidence of commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…This behavior is similar to that reported by Kopeika with regard to a supposed aerosol MTF (e.g., Kopeika et al, 2014), but this has been discounted numerous times. For example, Eismann and LeMaster (2013) developed an aerosol MTF but report it has negligible image blur effects and is nearly independent of spatial frequency.…”
Section: Baseline Annular-aperture Turbulence Effectssupporting
confidence: 77%
“…This behavior is similar to that reported by Kopeika with regard to a supposed aerosol MTF (e.g., Kopeika et al, 2014), but this has been discounted numerous times. For example, Eismann and LeMaster (2013) developed an aerosol MTF but report it has negligible image blur effects and is nearly independent of spatial frequency.…”
Section: Baseline Annular-aperture Turbulence Effectssupporting
confidence: 77%
“…The resolution loss caused by scattering in aerosols and fog has been well-studied for visible light. 1,6,7,13,[15][16][17][18][19][20][21][22][23] Some of the studies determined the effect of image blurring was negligible. 13,21,22 However, other studies demonstrated that image blurring significantly decreased image quality.…”
Section: Introductionmentioning
confidence: 99%
“…13,21,22 However, other studies demonstrated that image blurring significantly decreased image quality. 7,[17][18][19][20]23 Sadot et al 24 showed that scattering from aerosols significantly affected LWIR image quality in clear conditions. The previous measurements [10][11][12]14 of LWIR imaging performance through fog did not account for the resolution degradation cause by blurring.…”
Section: Introductionmentioning
confidence: 99%